The challenges facing the families of Emirati martyrs and mechanisms to reduce them - ALMansoori, Mariam; Al-Halalat, Khalil (Al-Adab Journal, 2025)
The study aims to identify the challenges facing the families of Emirati martyrs and the mechanisms to reduce them, which is represented by clarifying the challenges facing the wife and children and presenting the social challenges facing the family as a whole and the most important humanitarian needs of the families of the martyrs and their children. The study revealed many challenges facing the families of martyrs, including challenges resulting from different roles, challenges of withdrawal and social isolation, social and psychological challenges. Among the findings of the study is that the most important humanitarian needs that must be available to the families of martyrs are the provision of various supportive services, such as: legal consultations, psychological services, and ensuring that the concerned authorities fully fulfill their role in helping these families. One of the most important recommendations of the study is the need to provide specific mechanisms to reduce these challenges.